Complex syntax and working memory in children with specific learning difficulties. Issue 4 (August 2020) - Stanford, Emily; Delage, Hélène
Working memory (WM) limitations are frequently reported for children with specific learning disorder (SLD). However, WM capacity influences more than literacy and numeracy, as research highlights the contribution of WM to language development, in particular syntax. In this article, the authors study the effect of syntactic intervention, i.e. syntactic elements intervening between filler and gap, on comprehension in children with SLD and evaluate the relationship of this effect to WM capacity. Specifically, they assess how these children comprehend wh -questions and relative clauses. Additionally, they examine how comprehension relates to WM, measured by backward digit recall. The authors report that a subgroup of children with SLD struggle to comprehend structures containing intervention, and that WM capacity influences performance in SLD. Their conclusion is that computing a syntactic relation in which a moved object and an intervening subject share a featural specification taxes the processing system of children with SLD who have WM limitations. Thus, syntactic difficulties, although not typically associated with SLD, may form part of the SLD profile, especially when WM capacity is reduced.